The Reality of the Application of Social Networks in the Educational Environment. The Case of a Ceuta Teaching Cooperative - López-Belmonte, Jesús (2020)
The current world is going through a digitalization process. Considering this paradigm allows saying that social networks are becoming a sophisticated and necessary tool in relations among people. This type of means provides the user with a wide range of functionalities based on interaction and communication with other individuals in society. If it is applied in the educational environment, social networks encourage new forms of learning with a high motivating component on the part of the students. The research is carried out in a teaching cooperative of the Autonomous City of Ceuta, Spain. This kind of education center pursues the quality and innovation in the services they offer. This study seeks to understand the use of social networks for educational purposes in a cooperative educational center. In order to carry out this process, a sample of 40 teachers and 80 students was taken, using a mixed method from a quantitative approach, through questionnaires and a qualitative one, through semi-guided personal interviews. The most significant results reveal that 85% of teachers present unfavorable opinions about the use of social networks in the school environment, and, on the other hand, 96% of students are in favor of including these new tools in the learning process. It is concluded that, although the teaching cooperative seeks innovation among its principles, the teaching groups are not willing to include these methodologies in their didactic repertoire.